Adsorption of Pb(II) onto xanthated and hydrogen peroxide modified rubber (Hevea brasiliensis) leaf powder / Wan Khaima Azira Wan Mat Khalir - Wan Mat Khalir, Wan Khaima Azira (2013)
Two types of chemical modifications on rubber leaf powder were performed in order to evaluate the Pb(II) adsorption capacity by xanthation and oxidation processes. Pb(II) adsorption study was investigated under batch and fixed bed column modes. The amount of Pb(II) adsorbed increased with increasing pH, contact time and initial Pb(II) concentration but decreased with increasing adsorbent dosage, ionic strength and temperature for xanthated rubber leaf powder (XRL) and hydrogen peroxide rubber leaf powder (HPRL). The adsorption kinetics of Pb(II) by XRL and HPRL were fitted well with pseudo second order model suggesting that chemisorption could be the rate determining step in Pb(II) adsorption. The equilibrium time was achieved within 60 min for XRL and 90 min for HPRL. Adsorption of Pb(II) followed Langmuir isotherm model with the monolayer adsorption capacities of 166.7 mg/g by XRL and 52.6 mg/g by HPRL, respectively. The optimum adsorption process occurred at pH 4, shaking rate of 120 stroke/min and temperature of 303 K. The adsorption process was found to be exothermic for both adsorbents. The amount of Pb(II) adsorbed decreased in the presence o f Cu(II) ions. Pb(II) ions showed higher selectivity compared to Cu(II) ions in the binary systems. EDTA was more effective in releasing Pb(II) from XRL surface than HC1 but HPRL desorbed well in HC1. Possible mechanisms involved in the Pb(II) adsorption by XRL and HPRL were ion exchange, complexation and physical adsorption as supported by FTIR spectra, thermodynamic, ion exchange and desorption studies. Fixed bed column data was fitted well with the Thomas and Yoon-Nelson models with correlation coefficients of (R ) > 0.96 for both adsorbents.